Teaching Materials Science and Engineering (MSE) in the pre-college classroom as a vehicle for NGSS implementation - Granucci, Nicole; Jenkins, Carol; Bauer, Melanie; Gard, Ashley L.; Pinkerton, Bryn; Broadbridge, Christine (MRS Advances, 2017)
Adoption of Materials Science and Engineering (MSE) into the pre-college classroom is an ideal strategy for addressing Next Generation Science Standards (NGSS), specifically the Science and Engineering Practices. MSE offers core science and engineering topics that can be incorporated into existing Science, Technology, Engineering, and Mathematic (STEM) curricula through teaching modules. Using MSE as a teaching vehicle, the Center for Research on Interface Structures and Phenomena (CRISP) conducted a series of small-scale studies of its teacher professional development workshops and a student summer program, along with related teaching modules, in an effort to measure the contribution MSE has on students and K-12 STEM educators. Based on participant survey feedback, CRISP found improvement in students' MSE knowledge, interests, and career goals. For teachers, in addition to improving their MSE knowledge, they also increased their comfort and confidence in teaching MSE concepts in their classroom. These results provide evidence for the use of MSE modules as productive teaching tools for NGSS Science and Engineering Practices, as well as producing workforce-competitive STEM students. Copyright © Materials Research Society 2017.
1 citations (Crossref) [2023-10-31]
Keywords: Aerogels; Curricula; Education; Government interactions; Interface structures; Materials science and engineering; STEM (science; technology; engineering and mathematics); Science; technology; engineering; and mathematics; Science and engineering; Science standards; Standards; Students; Surveys; Teacher professional development; Teaching; Teaching materials; aerogel; dept.phy; education; government interactions; peer-reviewed

Noble metal high entropy alloys - Sohn, Sungwoo; Liu, Yanhui; Liu, Jingbei; Gong, Pan; Prades-Rodel, Silke; Blatter, Andreas; Scanley, B. Ellen; Broadbridge, Christine C.; Schroers, Jan (Scripta Materialia, 2017)
A series of noble metal high entropy alloys with up to six constituent elements has been produced by casting. PtPdRhIrCuNi forms single-phase face-centered cubic solid solution, and its stability is confirmed by annealing experiments. This alloy deforms homogeneously to ~30% to a high ultimate compression strength of 1839MPa. We discuss rules for the formation of single-phase solid solution.
70 citations (Crossref) [2023-10-31]
Keywords: Annealing experiments; Compressive properties; Compressive property; Constituent elements; Entropy; FCC structure; Face-centered cubic; Fcc structures; High entropy alloys; Phase stability; Precious metals; Single phase; Solid solution; Solid solutions; Ultimate compression; dept.phy

Determination of critical cooling rates in metallic glass forming alloy libraries through laser spike annealing. - Bordeenithikasem, Punnathat; Liu, Jingbei; Kube, Sebastian A; Li, Yanglin; Ma, Tianxing; Scanley, B Ellen; Broadbridge, Christine C; Vlassak, Joost J; Singer, Jonathan P; Schroers, Jan (Scientific reports, 2017)
The glass forming ability (GFA) of metallic glasses (MGs) is quantified by the critical cooling rate (R C). Despite its key role in MG research, experimental challenges have limited measured R C to a minute fraction of known glass formers. We present a combinatorial approach to directly measure R C for large compositional ranges. This is realized through the use of compositionally-graded alloy libraries, which were photo-thermally heated by scanning laser spike annealing of an absorbing layer, then melted and cooled at various rates. Coupled with X-ray diffraction mapping, GFA is determined from direct R C measurements. We exemplify this technique for the Au-Cu-Si system, where we identify Au56Cu27Si17 as the alloy with the highest GFA. In general, this method enables measurements of R C over large compositional areas, which is powerful for materials discovery and, when correlating with chemistry and other properties, for a deeper understanding of MG formation.
44 citations (Crossref) [2023-10-31] Place: England Bordeenithikasem, Punnathat. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Liu, Jingbei. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Kube, Sebastian A. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Li, Yanglin. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. Ma, Tianxing. Department of Mechanical and Aerospace Engineering, Rutgers University, Piscataway, New Jersey, 08854, USA. Scanley, B Ellen. Department of Physics, Southern Connecticut State University, New Haven, Connecticut, 06515, USA. Broadbridge, Christine C. Department of Physics, Southern Connecticut State University, New Haven, Connecticut, 06515, USA. Vlassak, Joost J. School of Engineering and Applied Science, Harvard University, Cambridge, Massachusetts, 02138, USA. Singer, Jonathan P. Department of Mechanical and Aerospace Engineering, Rutgers University, Piscataway, New Jersey, 08854, USA. Schroers, Jan. Department of Mechanical Engineering and Materials Science, Yale University, New Haven, Connecticut, 06511, USA. jan.schroers@yale.edu. Erratum in (EIN)
Keywords: dept.phy; peer-reviewed